122 "It's okay with our culture but were in a different place and we have to show respect": Marshallese migration and the impact on exclusive breastfeeding initiation. (April 2022) - Ayers, Britni L.; Purvis, Rachel S.; Bogulski, Cari A.; Kim Yeary, Karen H.; McElfish, Pearl Anna
Abstract : OBJECTIVES/GOALS: Pacific Islanders have some of the lowest rates of initiation and duration of exclusive breastfeeding compared to other racial women once they migrate to the United States. The purpose of this study is to identify infant feeding initiation, beliefs, and experiences of Marshallese women living in the United States soon after delivery. METHODS/STUDY POPULATION: This study used an exploratory, descriptive qualitative design with 36 Marshallese women residing in the United States from July 2019 to July 2020. A Community Based Participatory Research Approach was used to design and implement the study. This approach enables the respect and integration of Marshallese cultural values and practices into every aspect of the research All study plans and documents – including recruitment plans and forms, consent plans and forms, retention plans, quantitative surveys, and qualitative interview guides – were developed in partnership with Marshallese research team members. RESULTS/ANTICIPATED RESULTS: Two themes emerged: 1) Infant Feeding Initiation and Practices; and 2) Concerns of Breastfeeding in Public. Within the first theme, two subthemes emerged: 1) Breast and Formula-Feeding; and 2) Return to Work. Within the second theme, two subthemes emerged: 1) Personal Beliefs about Breastfeeding in Public; and 2) Acculturation and Breastfeeding in Public. DISCUSSION/SIGNIFICANCE: This is the first study to document beliefs about exclusive breastfeeding initiation among Marshallese women living in the United States. Findings from this study can be used to develop health education programs to improve exclusive breastfeeding and can be used to stimulate future research in the area of breastfeeding among Pacific Islander women.